Surface modification of W–V alloy exposed to high heat flux helium neutral beams. (3rd July 2018) - Wang, Jun; Li, Chun; Yuan, Yue; Greuner, Henri; Cheng, Long; Lu, Guang-Hong
Abstract: Surface modification of tungsten vanadium (W–V) alloy under high heat flux helium particle bombardment has been studied. W–5 wt.% V samples were irradiated by repeated helium pulses at a peak surface temperature of 900 °C and 1800 °C, respectively, in the neutral beam facility GLADIS. The effect of helium fluence on the surface morphology changes was investigated by increasing the helium fluence from 1  ×  10 22 m −2 – 2  ×  10 22 m −2 . Blistering is the typical structure after the repeated helium pulses loading at 900 °C, and it becomes more severe with increased fluence. A porous structure becomes dominant at 1800 °C. An evolution of a porous structure to coral-like structure is observed as fluence increases. In addition, the three typical regions in the W–5V, W-enriched region, W–V solid solute region, and V-enriched region, exhibit different damage features. The W–V solid solute region shows better surface damage resistance compared to the other two regions.